Optimality Conditions for Nondifferentiable Minimax Programs and Vector Optimization Problems - Huyen, Duong Thi Kim; Kim, Do Sang; Yen, Nguyen Dong (Journal of optimization theory and applications, 2024)
First-order sufficient optimality conditions in terms of Lagrangian functions and Lagrange multipliers for nondifferentiable minimax programs and vector optimization problems in an Asplund space setting are obtained in this paper. Two illustrative examples are given. Our results implement the first-order necessary optimality conditions of Chuong and Kim (Ann Oper Res 251:73–87, 2017).